Multidisciplinary team meetings for patients with complex extremity defects: a retrospective analysis of treatment recommendations and prognostic factors for non-implementation - Kotsougiani-Fischer, Dimitra; Fischer, Sebastian; Warszawski, Jan; Grützner, Paul Alfred; Reiter, Gregor; Hirche, Christoph; Kneser, Ulrich (BMC surgery, 2021)
This study aimed to assess a multidisciplinary team (MDT) meeting approach for the management of patients with complex extremity defects, analyze treatment recommendations, and evaluate factors influencing non-implementation.